Development of failure assessment methodology for lead-free electronic assembly - Che, Fa Xing (2008)
In this study, reliability test and analysis methodology for lead-free (Pb-free) soldered assemblies subjected to thermal cycling, cyclic bend, drop impact and vibration loadings are investigated. Finite element analysis (FEA) is used as a numerical modeling tool for simulating solder micro-deformation and integrated with solder fatigue failure analysis assessment. In this project, a failure assessment methodology for modeling Pb-free (and Pb-based) soldered assemblies is proposed.